Mental health problems and impact on youth minds during the COVID-19 outbreak: Cross-sectional (RED-COVID) survey - Deepak Nathiya; Pratima Singh; Supriya Suman; Preeti Raj; Balvir Singh Tomar (Wolters Kluwer Medknow Publications, 2020)
Introduction: The COVID-19 outbreak had impacted humankind with herculean force. Extensive Indian population which comprises youths are going through psychological resilience due to isolation, contact transmission, and economic crisis. Methods: A cross-sectional study among youth Indian citizens aged 15-30 years through social media platforms was conducted. The survey instrument consisted of demographic characteristics, assessment psychological impact by Depression, Anxiety and Stress-21 scale, and four items on COVID-19 stressors. Results: Out of 684 responses from red containment zones, 474 participants completed the study. Overall, moderate-to-severe stress, anxiety, and depression were 37.36%, 30.89%, and 24.63% in youths, respectively. Mental health outcomes were associated with female gender (odds ratio [OR] = 2.76, 95% confidence interval [CI]: 1.70-4.46), marital status (OR = 2.30, 95% CI: 1.47-3.88), residence in rural area (OR = 2.89, 95% CI: 1.74-4.78), and postgraduate qualification (OR = 1.49, 95% CI: 0.74-3.36). Economical stressors, physical illness, and changes in daily life were found to be positive predictors of mental health problems. Conclusion: Our finding suggested requirement psychological intervention targeting youth living in rural areas especially women through government schemes irrespective of educational status.